Motor function in Rett syndrome: comparing clinical and parental assessments. (26th November 2018) - Rodocanachi Roidi, Marina L; Isaias, Ioannis U; Cozzi, Francesca; Grange, Francesca; Scotti, Fabrizia M; Gestra, Valentina F; Gandini, Alessandra; Ripamonti, Enrico
Abstract : Aim: To describe a new clinical tool, the Rett Syndrome Motor Evaluation Scale (RESMES) and to assess (loco‐)motor function in people with Rett syndrome (RTT). Method: Formal assessment provided by physicians was followed by parents' direct observation at home using the RESMES. Sixty females (mean [SD] age 12y 5mo [8y 9mo], range 3–40y) with a clinical diagnosis and genetically determined RTT participated in the study. Spearman's/Pearson's coefficients assessed the correlation between the clinicians' and caregivers' evaluations, as well as the correlation of RESMES scores with other scales, namely the Pain Assessment in Advanced Dementia, the Rett Assessment Rating Scale, the Modified Ashworth Scale, and hand function (assessed with a scale of evaluation of purposeful hand function). Scores provided by parents and clinicians were tested statistically by Mann–Whitney U test. Results: Approximately 88% of patients had moderate to severe RTT symptoms and, on average, moderate motor impairment based on the RESMES. RESMES total scores provided by clinicians and caregivers were highly correlated ( r =0.91), as were the subscale scores. Postural transition was a critical area of the RESMES, where parents systematically provided lower scores than clinicians, indicating milder degrees of disability. Severity of scoliosis and mutation type emerged as significant predictors of motor function. Interpretation: The RESMES characterized the (loco‐)motor impairments of the patients with RTT well. It also showed a close correlation between the evaluations of clinicians and caregivers, with the possible exception of postural transition tasks, which should be carefully addressed in a clinical setting. The type of mutation and presence of scoliosis should be evaluated, as they predicted the ability to walk. What this paper adds: Caregivers at home can reliably assess motor function in Rett syndrome using the Rett Syndrome Motor Evaluation Scale (RESMES). RESMES scores provided by clinicians and parents were highly correlated. The severity of scoliosis and the genetic mutation predicted standing and walking abilities. What this paper adds: Caregivers at home can reliably assess motor function in Rett syndrome using the Rett Syndrome Motor Evaluation Scale (RESMES). RESMES scores provided by clinicians and parents were highly correlated. The severity of scoliosis and the genetic mutation predicted standing and walking abilities. This article is commented on by Lotan on page864 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Resumen: Función motora en el síndrome de Rett: comparación de evaluaciones clínicas y parentales: Objetivo: Describir una nueva herramienta clínica, la Escala de Evaluación Motora del Síndrome de Rett (RESMES) y evaluar la función motora (locomotora) en personas con síndrome. de Rett (RTT). Metodo: La evaluación formal proporcionada por los médicos fue seguida por la observación directa de los padres en el hogar utilizando los RESMES. Sesenta mujeres (edad media 12 años 5 meses[DS =8 años 9 meses], rango 3‐40 años) con diagnóstico clínico y genético de RTT participaron en el estudio. Los coeficientes de Spearman / Pearson evaluaron la correlación entre las evaluaciones de los médicos y los cuidadores, así como la correlación de las puntuaciones de RESMES con otras escalas, como la Evaluación del Dolor en la Demencia Avanzada (Pain Assessment in Advanced Dementia), la Escala de Calificación de la Evaluación de Rett (Rett Assessment Rating Scale), la Escala de Ashworth modificada y la función de la mano (evaluado con una escala de evaluación de la función voluntaria de la mano). Las puntuaciones proporcionadas por los padres y los clínicos se evaluaron estadísticamente mediante la prueba U de Mann‐Whitney. Resultados: Aproximadamente el 88% de los pacientes tenían síntomas de RTT de moderados a severos y, en promedio, una discapacidad motora moderada basada en los puntajes de RESMES. Se encontró una correlación muy alta (r = 0, 91) entre los puntajes totales de RESMES proporcionados por los médicos y cuidadores, al igual que los puntajes con las otras escalas. La transición postural fue un área crítica de RESMES, donde los padres proporcionaron sistemáticamente puntuaciones más bajas que los clínicos, lo que indica grados más leves de discapacidad. La gravedad de la escoliosis y el tipo de mutación fueron factores significativamente predictivos de la función motora. Interpretación: Los puntajes de RESMES caracterizaron bien las alteraciones motoras de las pacientes con RTT. Se encontró una estrecha correlación entre las evaluaciones de los médicos y los cuidadores, con la posible excepción de los cambios postural, que deben evaluarse con cuidado en un entorno clínico. Se debe considerar el tipo de mutación y la presencia de escoliosis, ya que predijeron la capacidad de caminar. Abstract : Função motora na síndrome de Rett: comparando avaliações clínicas e dos pais: Objetivo: Descrever uma nova ferramenta clínica, a Escala de avaliação motora da síndrome de Rett (RESMES) e avaliar a função (loco)motora em pessoas com síndrome de Rett (RTT). Método: A avaliação formal por médicos foi seguida por observação direta dos pais em casa usando a RESMES. Sessenta meninas (média [DP] idade 12a 5m [8a 9m], variação 3–40a) com diagnóstico clínico e RTT determinada geneticamente participaram no estudo. Coeficientes de Spearman/Pearson avaliaram a correlação entre avaliações dos clínicos e cuidadores, assim como as correlações dos escores na RESMES com outras escalas: Avaliação da Dor na Demência avançada (Pain Assessment in Advanced Dementia), Escala de Classificação de Rett (Rett Assessment Rating Scale), a Escala de Ashworth Modificada, e função manual (avaliada com uma escala de avaliação da função manual voluntária). Os escores fornecidos pelos pais e clínicos foram testados estatisticamente com o teste de Mann–Whitney U . Resultados: Aproximadamente 88% dos pacientes tinham sintomas de RTT de moderados a severos e, em média, comprometimento motor moderado na RESMES. Os escores totais da RESMES dados pelos clínicos e cuidadores foram altamente correlacionados ( r =0, 91), assim como os escores das subescalas. Transição postural foi uma área crítica da RESMES, em que pais sistematicamente ponturam mais baixo que os clínicos, indicando graus mais leves de incapacidade. A severidade da escoliose e tipo de mutação emergiram como preditores significativos da função motora. Interpretação: A RESMES caracterizou bem as deficiências (loco) motoras de pacientes com RTT. Também mostrou correlação próxima entre as avaliações de clínicos e cuidadores, com a possível exceção das tarefas de transição postural, as quais devem ser cuidadosamente abordadas no contexto clínico. O tipo de mutação e presença de escoliose devem ser avaliados, pois predizem a capacidade de andar.